A comparative framing analysis of online print and broadcast media coverage of the Israel-Palestine conflict (October 2023 - June 2024) - Cahatol, Marilyn Ogardo; De Castro, Maverick M.
The study compared the coverage of the Israel-Palestine conflict by print and broadcast news organizations in the Philippines by looking at the peace and war journalism frames (Galtung, 2013) and generic frames (Semetko and Valkenburg, 2000) present in the stories. It consisted of the content analysis of 1478 stories by PhilStar.com. lnquirer.net. GMA Network's 24 Oras, and ABS-CBN's TV Patrol, tackling the conflict from October 2023 to June 2024. Print covered the majority of the total output. Compared to print, broadcast organizations always used local sources in their reportage. There were no dominating frames in print as both organizations depicted different focuses in their coverage. For broadcast, OFW remained the dominant frame for both news organizations. For the war and peace journalism frames present in the news articles and reports, both print and broadcast exhibited the peace journalism indicators of truth-telling and suffering of the people. However, all four failed to perform the peace journalism traits of explaining conflict formation and solution-oriented narrative. Pertaining to the generic frames, the coverage had a huge focus on the Human-Interest frame for print and broadcast, together with the responsibility frame. The economic consequence and morality frame were not highlighted at all.